Hubungan Antara Kekuatan Lengan Dan Koordinasi Mata-Tangan Terhadap Kemampuan Smash Dalam Permainan Bulutangkis - Hasruddin (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2020)
This research is a descriptive research type. This study aims to see: see the relationship between arm strength and smash ability in badminton, hand eye coordination with smash skills in badminton games, see the relationship between arm strength and hand eye coordination with smash ability in badminton. The population is the eighth grade students of SMPN 19 Hulu Sungai Tengah while the sample used is the seventh grade students of SMPN 6 Kotabaru as many as 35 people. The technique of determining the sample is by means of a lottery (random sampling technique). The data analysis technique used is descriptive analysis and inferential analysis through the SPSS 22 program at a significant level of Î± 0.05. The results showed that; There is a significant relationship between arm strength and smash ability in badminton of 0.674, there is a significant relationship between hand eye coordination and smash ability in badminton at 0.527, there is a significant relationship jointly between arm strength and hand eye coordination ability to smash. in the badminton game F = 22,258